Early Warning Scores as a Predictor of Mortality in Non Comorbid COVID-19 Patient - Rahmawati, Anita; Nurmawati, Thatit; Arsa, Sandi Alfa Wiga; Fata, Ulfa Husnul; Murti, Rahma (Journal of Ners and Midwifery, 2024)
There are several non-comorbid COVID-19 patients lead to mortality, but the risk factors that affect it have not been widely discussed in research. Treatment of COVID-19 patients focuses more on patients with comorbidities. This study aimed to check the effectiveness of Early Warning Scores (EWS) assessment to predict the mortality of non-comorbid COVID-19 patients. The method of the study was a case study research with a retrospective approach using secondary data, namely the patient's medical record status. This study took medical record data from 262 patients confirmed positive for non-comorbid COVID-19 who were hospitalized at Ngudi Waluyo Wlingi Hospital from July to September 2021. The multivariate data analysis used multiple linear regression tests to simultaneously test the relationship of the independent variables (age, gender, and Early warning score) to the dependent variable (mortality). The statistical analysis result showed the correlation between gender, age, and assessment with mortality, each of which has a p-value of 0.000, meaning that each of these variables has a relationship with mortality. If a simultaneous test (F test) is carried out, the p-value is 0.000, meaning that gender, age, and EWS simultaneously affect mortality. The coefficient of determination or R square of 0.773 means that gender, age, and EWS simultaneously influence mortality by 77.3%. Early Warning Scores (EWS) assessment influenced the mortality of non-comorbid COVID-19 patients. The highest contribution affecting mortality was the EWS assessment. The contribution of influence on sex and age is relatively the same.